The Roles of Knowledge Providers, Knowledge Recipients, and Knowledge Usage in Bridging Structural Holes. Issue 2 (27th October 2018) - Ozer, Muammer; Zhang, Guangxi
Abstract : Studies have suggested that firms can benefit from bridging two or more otherwise disconnected firms in their ego networks (i.e., structural holes) as a potentially useful source of external knowledge for innovation. However, past research also noted that the relationship between bridging structural holes and firm innovation varies significantly. Building on the earlier research that has examined the industrial, structural, and institutional dimensions of this relationship, the purpose of this research is to study how the different characteristics of the external knowledge provided by bridging structural holes in a focal firm's ego network might moderate the relationship between bridging structural holes and firm innovation. Using longitudinal data from the U.S. computer industry, this study showed that focal firms that bridged otherwise disconnected firms in their ego networks enjoyed higher levels of innovation. In addition, it showed that this relationship was particularly stronger when the focal firms and the disconnected firms that they bridged operated in similar rather than different markets but when the focal firms and the disconnected firms worked on different rather than similar technological domains. The results also revealed that the relationship was stronger when the focal firms' knowledge specialization was low rather than high and when the focal firms emphasized incremental rather than breakthrough innovation. These findings show companies how they can benefit from bridging otherwise disconnected firms in their ego networks and help them make more informed decisions pertaining to such bridging activities.